In Life as in Sport: Implications of a Program to Educate Spanish Youth on Values - Smith-Palacio, Eulisis; Alcalá-Recuero, Jesús; Lamoneda-Prieto, Javier (Frontiers in Education, 2022)
This research examined the effects of the Delphi method on self-control and explored the students' opinions. 305 young people (55% girls) with an average age of 11.6 years (+/- 0.69) and who were enrolled in public schools in the central area of Spain took part. A quasi-experimental single-group design was followed, with pre-test and post-test measures, subsequently employing a mixed quantitative-qualitative analysis approach. The CACIA questionnaire was used in which the students' perception was assessed. A single level of treatment was undertaken, with intact natural groups that experienced twenty didactic sessions on indoor football. The quantitative results showed an improvement in personal feedback, deferring reward, criterion self-control and process self-control. The qualitative analysis of student responses yielded four topics: Conflict resolution, respect, honesty and prosociality; in two areas: Sport activity and personal life.